알레르기 비염 청소년의 수면만족감 영향요인 - 김효정; Kim, Hyo Jung (韓國學校保健學會誌, 2019)
Purpose: This study was conducted to examine the factors that influence sleep satisfaction among adolescents with Allergic Rhinitis in Korea. Methods: Data were obtained from 21,480 subjects who completed the 2018 14th Korea Youth Risk Behavior Web-based Survey. The data were analyzed using complex samples logistic regression with PASW 18.0. Results: The factors influencing sleep satisfaction were gender, grade, academic achievement, economic status, living arrangement, physical activity, drinking, smoking, stress, depression, perceived health status and perceived body image. Conclusion: It is necessary to develop interventions considering general and health-related characteristics in order to improve sleep satisfaction among adolescents with allergic rhinitis.